Effects of Fisetin, a Plant-Derived Flavonoid, on Response to Oxidative Stress, Aging, and Age-Related Diseases in Caenorhabditis elegans - Suhyeon Park; Bo-Kyoung Kim; Sang-Kyu Park (MDPI AG, 2022)
Fisetin (3,3',4',7-tetrahydroxyflavone), a flavonoid abundant in various fruits and vegetables, including apple, strawberry, and onion, shows several beneficial effects such as anti-oxidant, anti-inflammatory, and anti-tumor effects. The free radical theory of aging suggests that age-related accumulation of oxidative damage is the major cause of aging and that decreasing cellular oxidative stress can regulate aging. Here, we investigated the effects of dietary supplementation with fisetin on the stress response, aging, and age-related diseases. Fisetin reduced the cellular ROS levels and increased the resistance to oxidative stress. However, the response to UV irradiation was not affected by fisetin. Both the mean and maximum lifespans were significantly extended by fisetin; lifespan extension by fisetin was accompanied by reduced fertility as a trade-off. Age-related decline in motility was also delayed by supplementation with fisetin. Amyloid beta-induced toxicity was markedly decreased by fisetin, which required DAF-16 and SKN-1. Reduced motility induced by a high-glucose diet was completely recovered by supplementation with fisetin, which was dependent on SKN-1. Using a Parkinson's disease model, we showed that degeneration of dopaminergic neurons was significantly inhibited by treatment with fisetin. Genetic analysis revealed that lifespan extension by fisetin was mediated by DAF-16-induced stress response and autophagy. These findings support the free radical theory of aging and suggest that fisetin can be a strong candidate for use in novel anti-aging anti-oxidant nutraceuticals.